Quality and extent of adherence on internal medicine discharge letters in a regional hospital in South Africa to prescribed guidelines. A retrospective audit - Nya, Anthony (Department of Public Health and Family Medicine, 2020)
Background: Hospital discharge letters are an essential part of good patient record keeping that ensures transmission of the healthcare information of a patient from the hospital of admission to the primary care practitioner. These letters were traditionally handwritten, but the medical ward in Victoria hospital Wynberg in adapting to current progress in clinical record keeping has transited from paper to the use of electronic discharge letters. Objectives: To audit the structure and contents of the electronic discharge summaries and find out to what extent they meet universally accepted criteria. Methodology: A retrospective clinical record audit of 60 patient records was conducted, spanning a period of 12 months (January-December) of 2018. Sequential sampling was used to select five folders from each months’ discharge records, making a total study sample of 60 patient records. A checklist of prescribed criteria was developed and used to collect data which was analysed descriptively. Ethical approval was obtained from University of Cape Towns’(UCT) Human Research Ethics Committee (HREC) and the Western Cape Government Provincial Research Committee. Electronic discharge letters compiled in the period 1 January- 31 December 2018 with corresponding folders found properly indexed in the medical records department were included in the sample, while discharge letters where the folders could not be found were excluded, as were the folders of patients who died during the hospital admission. Results: Nearly all clinical records contained biodata (100%), contact details (93%) and clinical details (93%). Only two-thirds of the folders contained information on other diagnoses(67%) and investigations matched clinical issues 63%.). The least compliant category was medication changes(53%), with just under half the folders containing this information. Conclusion: This study found that clinical records met 67% of the standards that define clinical and medico-legal compliance in the internal medicine ward in Victoria Hospital Wynberg. Several areas for future intervention were identified. A useful audit tool was also developed for ongoing quality improvement cycle.